S1P-S1PR1 Signaling: the “Sphinx” in Osteoimmunology - Xiao, Lan; Zhou, Yinghong; Friis, Thor; Beagley, Kenneth; Xiao, Yin (Frontiers in Immunology, 2019)
Bone remodeling is strictly regulated by immune modulators to maintain the balance between bone resorption and formation. This fundamental interaction between the immune and skeletal systems termed as osteoimmunology is regulated by numerous modulators. Among these modulators the pleiotropic sphingolipid metabolite, S1P, together with its cognate receptors, the S1PRs, are known to be involved in the regulation of both immune system and bone remodeling. S1P-S1PR1 signaling is also considered an important signaling pathway capable of inducing inflammatory response that modulates both osteoclastogenesis and osteogenesis. Its role in bone remodeling can be direct by targeting both osteoclastogenesis and osteogenesis, however, inflammatory cell population and polarization in both adaptive immune (T cell subsets) and innate immune cells (macrophages) are also regulated by this signaling axis, indicating that S1P-S1PR1 signaling might take part in the maintenance of continuous bone turnover under physiological conditions, while lead to the pathogenesis of bone deformities during inflammation. In this review, we summarized the immunological regulation of S1P-S1PR1 signal axis during bone remodeling with an emphasis on how osteo-immune regulators are affected by inflammation, an issue with relevance to chronical bone disorders such as rheumatoid arthritis and periodontitis.